CLUES TO THE ORIGIN OF INTERPLANETARY DUST PARTICLES FROM THE ISOTOPIC STUDY OF THEIR HYDROGEN-BEARING PHASES - Aleon J.; Engrand C.; Robert F.; Chaussidon M. (My University, 2001)
Ion microprobe quantitative imaging was performed for H, D, 12,13C, 16,18O, 27Al, and 28,29,30Si in five stratospheric particles with a 1.5 x 1.5 μm spatial resolution to determine the carriers of high D/H ratios and to give new clues about the parent bodies of interplanetary dust particles (IDPs). Among these particles, four appear to be of extraterrestrial origin. Using imaging, the large variations of D/H ratios can be correlated at the micrometer scale with chemical composition so that endmembers can be identified. From the systematics of variation of C/H and D/H ratios, water present as hydroxyls in phyllosilicates (at C/H = 0) and three different types of organic matter (OM1, 2, and 3) were identified. Water exhibits D/H ratios lying in the chondritic domain (D/H ~150 x 10-6), whereas OMs are enriched in deuterium. OM1 is similar to the macromolecular organic matter of carbonaceous chondrites (D/H = 250 x 10-6 and C/H = 1.5). OM2 (D/H = 1500 x 10-6 and C/H = 1.0) is close to cometary HCN. OM3 (D/H = 2000 x 10-6 and C/H = 3.0) is a highly condensed carbonaceous phase with no counterpart in known extraterrestrial objects. The C, O, and Si isotopic compositions are solar within +/- 10%.The identification of these phases allows a better understanding of the origin of D/H variations inferred for the protosolar nebula. The only mechanism that can explain such high D/H ratios is interstellar chemistry. However, D/H ratios in interplanetary dust organic matter remain lower than those measured in molecules from cold molecular clouds. This difference can be accounted for by an isotopic exchange with liquid water in IDP parent bodies. In addition, the close association of the chondritic component OM1 with the likely cometary component OM2 is evidence for a link between carbonaceous chondrites and comets. Although IDPs contain cometary organic matter, the water-D/H ratio is lower than that measured in comets (310 x 10-6). IDPs seem thus constituted of various materials formed over a large range of heliocentric distances.